GPS and GSM Based Engine Locking System Using Smart Password - Omanakuttan, A; Sreedhar, D; Manoj, A; Achankunju, A; Cherian, CM (International Journal of Computer Sciences and Engineering, 2025)
The smart engine locking system is an embedded system based intrusion detection system designed and implemented to prevent unauthorized access of vehicles while parking in insecure places. The proposed system incorporates a micro controller along with GSM and GPS modules. This instrument is installed in the engine of the vehicle whose current position is to be recorded and locked the engine in real time. Main objective of this instrument is to protect the vehicle from any unauthorized access by providing two locking status, theft mode and user mode. These two modes are controlled by Arduino UNO and GPS technology is used for finding current location of the vehicle. A GSM modem is also connected to the micro controller for sending message to the owner’s mobile if the vehicle is in theft mode. This system puts into the user mode if vehicle is handled by the owner or authorized persons, otherwise goes to theft mode. The most important concept in this design is introducing the mobile communications into the embedded system using GSM module. The entire design is on a single board.